The racial state : Germany 1933-1945 - Burleigh, Michael 1955- (Cambridge University Press, 1991)
Between 1933 and 1945 the Nazi regime in Germany tried to restructure a "class" society along racial lines. This book deals with the ideas and institutions that underpinned this mission, and shows how Nazi policy affected various groups of people, both victims and beneficiaries. The book begins with a serious discussion of the origins of Nazi racial ideology, and then demonstrates the way in which this was translated into official policy. It deals with the systematic persecution not only of the Jews, but also with the fate of lesser-known groups such as Sinti and Roma, the mentally handicapped, the "asocial," and homosexuals.--Publisher description